Socio-historical research and land tenure in South Africa: a case study of land tenure rights on the Northern Cape farm of Melkkraal - Jacobs, Cameron Lee (Department of Political Studies, 2014)
The aim of the research was to clarify and explain the land tenure relations of a farming community called Melkkraal situated in the Northern Cape such that development assistance could be rendered to them by the Department of Land Affairs (DLA).The Melkkraal farm has been owned by various members of the Kotze family since 1834 and through the process of testate and intestate succession has passed from one generation to the next. At present the farm is owned by seven members of the Kotze family in a co-ownership. However, it is also a home to twenty-six households of which three have a legal title to the land as co-owners. The remaining households have occupied the land through a haphazard process of acquiring oral permission from some of the co-owners and non-owning residents, some for as long as sixty five years. This has led to a tenure conundrum because the way in which the Melkkraal farm is registered means that neither the twenty six families who use the land, nor the seven co-owners can access the DLA assistance or effectively assert authority to make development decisions. As a result, the community requested the Surplus Peoples Project and the Environmental Monitoring Group (EMG) to advise them on the steps they would need to gain access to the DLA assistance and to better manage the land. During January 2004, SPP and EMG undertook to investigate and report on the nature and content of the rights of the members of the community in relation to the rights of the co-owners so that the community could be assisted to formulate a strategy for the achievement of their developmental objectives. In February 2004, SPP conducted an extensive research study on how the community members hold, use and transact rights in land. While participatory action research was the overall research paradigm, the particular research technique used for the Melkkraal case study was participatory rural appraisal (PRA). PRA is an action research tool or technique that involves community members defining and working to solve local concerns. As a result of the use of PRA the following research phases were drafted: The first phase of the research entailed the collection and analysis of archival data to develop an understanding of the co-ownership and its co-owners and to develop a genealogy of the co-ownership. The second phase entailed conducting field work at Melkkraal in terms of interviewing the heads of each household as well as an interview with the land management committee. Phase three entailed a follow up visit to Melkkraal, a presentation of a progress report, a participatory mapping session and a focus group workshop on the various land uses at Melkkraal. The final phase of the research included another follow up visit to Melkkraal, the completion of the research analysis and the development of a final report that was presented to the community. The final presentation entailed a workshop explaining the land rights of the various households and a discussion of the way forward. The research findings revealed that very little difference exists between the non-owning residents and the co-owners in terms of how land is used and transacted. This was attributed to the evolution of the social land ethic such that one can speak of the Melkkraal farm as a common property regime. Therefore, in practice there is no difference between a non-owning resident and a co-owner. The findings also revealed that just cause can be shown to apply for a declaratory order to invoke the Interim Protection of Informal Rights Act 31 of 1996. A successful application will mean that the existing informal rights in land of the non-owning residents will be elevated to the status of real rights in property.